PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMBANGUN BUDAYA SEKOLAH YANG INOVATIF DAN KOLABORATIF DI SMPN 2 LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Azmaniar, Yanti; Desmira, Srina; Gistituati, Nurhizrah; Rusdinal, Rusdinal; Nellitawati, Nellitawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Transformational leadership is a leadership style that has the power to transform organisational behaviour, values, and culture through a process of motivating, inspiring, and encouraging innovative thinking. In the context of schools, the transformational leadership of the headteacher is a key factor in creating a collaborative work culture and a sustainable climate of innovation. This article aims to analyse how transformational leadership plays a role in building an innovative and collaborative school culture at SMPN 2 Lubuk Alung, Padang Pariaman Regency. The research uses a qualitative method with a literature study, namely analysing theories, empirical findings, and relevant articles from the last 10 years. The results of the study show that transformational leadership is capable of creating an innovation-oriented school culture through an inspiring vision, teacher empowerment, intellectual stimulation, and individual attention. This leadership also strengthens teacher collaboration through the formation of learning communities, effective communication, and the provision of space for cross-subject cooperation. This article provides a comprehensive overview of the role of the principal as an agent of change and recommendations for SMPN 2 Lubuk Alung in building a sustainable innovative and collaborative school organisational culture.